Potential predictors of outcomes among hospitalized COVID-19 patients treated with convalescent plasma: a single-center study. Issue 4 (4th July 2021) - Chilimuri, Sridhar; Zahid, Maleeha; Mantri, Nikhitha; Sun, Haozhe; Saleh, Mohamed; Ashraf, Shoaib; Gongati, Sudharsan; Adrish, Muhammad
ABSTRACT: Background: The coronavirus disease 2019 pandemic is a major international public health crisis, which has led to over 3 million deaths as of April 2021. Several therapeutics have been tried for this deadly illness including antivirals, immunosuppressive agents and convalescent plasma (CP). In this study, we present our inner-city safety net hospital experience with CP therapy. Methods: This was a retrospective chart review of hospitalized patients with confirmed COVID-19 who were treated with CP. Results: A total of 60 patients received CP during the study period. The mean age for patients in this study was 58.95 years. The most common presenting symptoms were shortness of breath (85%) and cough (73%). Hypertension (65%) and diabetes mellitus (55%) were the most common comorbidities in our patients. In our multivariate regression analysis, male sex, nausea and loss of appetite at presentation were associated with improvement in oxygenation after CP. Total survival time, history of obstructive airway disease, home use of angiotensin-converting enzyme inhibitors and angiotensin-receptor blockers were associated with decreased survival, whereas Hispanic ethnicity showed a trend towards lower survival after CP therapy. Conclusions: Our study highlights several important characteristics of inner-city safety net hospital patient population who might benefit from CP therapy.